A high quality factor microwave dielectric ceramic material and preparation method thereof
By adopting the composite phase structure of magnesium titanate and calcium aluminosilicate in microwave dielectric ceramic materials and adding specific oxides as sintering additives, the existing materials are difficult to meet the needs of low loss and high quality factors at high frequencies and high temperatures, and ceramic materials with high quality factors, wide sintering temperature range and good temperature stability are achieved.
Patent Information
- Application Number
- CN202411977142.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing magnesium titanate matrix is difficult to meet the needs of low loss and high quality factors at high frequency and high temperature, affecting the performance and stability of microwave communication equipment.
Microwave dielectric ceramic materials with a composite phase structure, including composite materials of magnesium titanate (MgTiO3) and calcium aluminosilicate (CaAl2Si2O8) with a chain crystal structure, and oxides of Cu, B, Bi, V, Zn, Li and other elements are added as sintering additives during the sintering process.
The quality factor (Qf) value of the material is significantly improved, ensuring that the dielectric constant is between 20 and 22, the resonance frequency temperature coefficient is adjustable and the absolute value is ≤15ppm/℃, and the sintering temperature range is widened and production efficiency is improved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of microwave dielectric ceramic materials, and in particular, relates to a high quality factor microwave dielectric ceramic material and a preparation method thereof. Background Art
[0002] With the rapid development of the 5G mobile communication system industry and the launch of the development of 6G communication technology, mobile communication equipment has gradually become miniaturized and intelligent, and microwave dielectric electronic components have also been continuously developing in the direction of miniaturization and lightweight. At present, the demand for ultra-low-loss microwave circuits and devices at ultra-high frequencies in communication fields such as satellite communications, automotive communications, and electronic countermeasures continues to grow. In the design and production process of microwave ceramic components, it is also necessary to take into account both product performance and economic benefits. This is a huge challenge for the development of microwave dielectric ceramic materials.
[0003] Magnesium titanate is usually used in microwave dielectric ceramic material matrix due to its excellent electrical properties at high frequency and high temperature. In order to match the key technical requirements of future microwave dielectric ceramic development such as low loss and high quality factor, the magnesium titanate matrix cannot fully meet the requirements. Low loss can reduce the attenuation of signals in ceramic materials, thereby ensuring the stability and reliability of signal transmission. High quality factor is an important indicator to measure the energy storage and release capacity of ceramic materials, which directly affects the frequency selectivity and signal processing performance of the material; in addition, the efficient use of microwave components also requires high temperature stability, appropriate dielectric constant and wide sintering temperature support. Therefore, the development of a microwave dielectric ceramic material with a high quality factor and a wide sintering range is of great significance to ensure the stable transmission of microwave communications. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a high-quality factor microwave dielectric ceramic material and a preparation method; the microwave dielectric ceramic material has a composite structure of magnesium titanate with a perovskite phase and calcium aluminosilicate with a chain crystal structure, which can effectively improve the quality factor of the microwave dielectric ceramic material within a wide sintering temperature range.
[0005] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0006] On the one hand, the present invention provides a high-quality factor microwave dielectric ceramic material, which is a complex phase structure ceramic material, including a main crystalline phase and a secondary crystalline phase, wherein the main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.93 to 0.99; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.01 to 0.07.
[0007] Furthermore, the microwave dielectric ceramic material also includes a sintering aid, which accounts for 0.1 to 5 wt.% of the mass of the microwave dielectric ceramic material; the sintering aid is selected from at least one oxide of Cu, B, Bi, V, Zn, and Li.
[0008] Furthermore, the microwave dielectric ceramic material has a dielectric constant of 20 to 22, a quality factor Qf value of not less than 60000 GHz, and an adjustable resonant frequency temperature coefficient with an absolute value of ≤15 ppm / °C.
[0009] Another aspect of the present invention provides a method for preparing a high quality factor microwave dielectric ceramic material, comprising the following steps:
[0010] 1) The weighed materials MgO and TiO2 are mixed fully and then ball-milled, and after ball-milling, they are dried, sieved, put into a corundum crucible, and then pre-calcined at a temperature to obtain MgTiO3 powder;
[0011] 2) The weighed materials CaCO3, Al2O3, and SiO2 are mixed thoroughly and ball-milled, dried, sieved, put into a corundum crucible, and then pre-calcined at a temperature to obtain CaAl2Si2O8 powder;
[0012] 3) The MgTiO3 powder obtained in step 1) and the CaAl2Si2O8 powder obtained in step 2) are mixed in proportion, ball-milled, dried, granulated, sieved, pressed, and finally debinded and sintered to obtain the microwave dielectric ceramic material.
[0013] Furthermore, a sintering aid is added in step 3), and the sintering aid is selected from at least one oxide of Cu, B, Bi, V, Zn, and Li.
[0014] Furthermore, the pre-burning temperature in step 1) and step 2) is 800-1000° C., and the pre-burning time is 2-5 hours.
[0015] Furthermore, the granulation in step 3) is to mix the dried powder with a binder and then make micron-sized spherical particles; the binder used in the granulation is selected from at least one of polyvinyl alcohol solution, polyvinyl butyral solution, acrylic acid solution or methyl cellulose.
[0016] Furthermore, in step 3), the granular material is pressed into a cylinder with a diameter of 10 mm and a height of 6 mm.
[0017] Furthermore, the debinding process in step 3) is carried out at 600° C. for 2 hours.
[0018] Furthermore, the sintering process in step 3) is performed at 1280-1360° C. for 3-7 hours.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention adopts CaAl2Si2O8 and magnesium titanate composite to make its resonant frequency temperature coefficient reach the requirement of near zero, and the microwave dielectric ceramic material also has the following properties: 20≤εr≤22, quality factor Qf value≥60000, resonant frequency temperature coefficient τf≤15ppm / ℃.
[0021] The present invention also broadens the sintering temperature range of the ceramic material and improves the production efficiency of the product by appropriately adding a sintering aid. DETAILED DESCRIPTION
[0022] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] On the one hand, the present invention provides a high-quality factor microwave dielectric ceramic material, which is a complex phase structure ceramic material, including a main crystalline phase and a secondary crystalline phase, wherein the main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.93 to 0.99; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.01 to 0.07.
[0024] The microwave dielectric ceramic material also includes a sintering aid, which accounts for 0.1 to 5 wt.% of the mass of the microwave dielectric ceramic material; the sintering aid is selected from at least one oxide of Cu, B, Bi, V, Zn, and Li.
[0025] The microwave dielectric ceramic material has a dielectric constant of 20 to 22, a quality factor Qf value of not less than 60000 GHz, an adjustable resonant frequency temperature coefficient and an absolute value of ≤15 ppm / °C.
[0026] The method for preparing the high quality factor microwave dielectric ceramic material comprises the following steps:
[0027] 1) The weighed materials MgO and TiO2 are mixed fully and then ball-milled. After ball-milling, they are dried, sieved, put into a corundum crucible, and then pre-calcined to obtain MgTiO3 powder; the pre-calcination temperature is 800-1000°C, and the pre-calcination time is 2-5h;
[0028] 2) The weighed materials CaCO3, Al2O3, and SiO2 are mixed thoroughly and ball-milled, dried, sieved, and placed in a corundum crucible after ball milling, and then pre-burned at a temperature of 800 to 1000° C. for a pre-burning time of 2 to 5 hours to obtain CaAl2Si2O8 powder;
[0029] 3) The MgTiO3 powder obtained in step 1) and the CaAl2Si2O8 powder obtained in step 2) are mixed in proportion, ball-milled, dried, granulated, screened, pressed, and finally debinded and sintered to obtain the microwave dielectric ceramic material. In step 3), a sintering aid is also added, and the sintering aid is selected from at least one oxide of Cu, B, Bi, V, Zn, and Li; the granulation in step 3) is to mix the dried powder with a binder and then make micron-sized spherical particles; the binder used in granulation is selected from at least one of polyvinyl alcohol solution, polyvinyl butyral solution, acrylic acid solution or methyl cellulose; the sieved granules are pressed into a cylinder with a diameter of 10 mm and a height of 6 mm; the debinding process is to keep the temperature at 600°C for 2 hours, and the sintering process is to sinter at 1280-1360°C for 3-7 hours.
[0030] The dielectric constant microwave dielectric ceramic material can be applied to microwave components.
[0031] Example 1
[0032] The microwave dielectric ceramic material of the embodiment 1 is a composite ceramic material, including a main crystalline phase and a secondary crystalline phase, wherein the main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.93; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.07. The microwave dielectric ceramic material also includes a sintering aid CuO, and the sintering aid accounts for 5wt.% of the mass of the microwave dielectric ceramic material.
[0033] The method for preparing the high quality factor microwave dielectric ceramic material comprises the following steps:
[0034] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 800° C. for 5 hours to obtain MgTiO3 powder;
[0035] 2) According to the molar ratio of each element in the composition expression CaAl2Si2O8, the materials CaCO3, Al2O3 and SiO2 are weighed respectively, the materials are fully mixed and then ball-milled, and after ball-milling, they are dried, sieved and put into a corundum crucible, and then pre-calcined at a temperature of 900° C. for 5 hours to obtain CaAl2Si2O8 powder;
[0036] 3) The MgTiO3 powder obtained in step 1), the CaAl2Si2O8 powder obtained in step 2) and the sintering aid CuO are ball-milled and dried in proportion, and then granulated and sieved. The sieved granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm. The cylinders are first sintered at 600°C for 2 hours to remove binder, and then sintered at 1280°C for 7 hours to obtain the microwave dielectric ceramic material.
[0037] Example 2
[0038] The microwave dielectric ceramic material of Example 2 is a composite ceramic material, including a main crystalline phase and a secondary crystalline phase, wherein the main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.95; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.05. The microwave dielectric ceramic material also includes a sintering aid Li2O, and the sintering aid accounts for 4wt.% of the mass of the microwave dielectric ceramic material.
[0039] The method for preparing the high quality factor microwave dielectric ceramic material comprises the following steps:
[0040] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 830° C. for 4.5 hours to obtain MgTiO3 powder;
[0041] 2) According to the molar ratio of each element in the composition expression CaAl2Si2O8, the materials CaCO3, Al2O3 and SiO2 are weighed respectively, the materials are fully mixed and then ball-milled, and after ball-milling, they are dried, sieved and put into a corundum crucible, and then pre-calcined at a temperature of 850° C. for 5 hours to obtain CaAl2Si2O8 powder;
[0042] 3) The MgTiO3 powder obtained in step 1), the CaAl2Si2O8 powder obtained in step 2) and the sintering aid Li2O are ball-milled and dried in proportion, and then granulated and sieved. The sieved granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm, and are first sintered at 600°C for 2 h to remove binder, and then sintered at 1300°C for 6 h to obtain the microwave dielectric ceramic material.
[0043] Example 3
[0044] The microwave dielectric ceramic material of the third embodiment is a composite ceramic material, including a main crystalline phase and a secondary crystalline phase, wherein the main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.97; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.03. The microwave dielectric ceramic material also includes a sintering aid Bi2O3, and the sintering aid accounts for 2wt.% of the mass of the microwave dielectric ceramic material.
[0045] The method for preparing the high quality factor microwave dielectric ceramic material comprises the following steps:
[0046] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 850° C. for 4 hours to obtain MgTiO3 powder;
[0047] 2) According to the molar ratio of each element in the composition expression CaAl2Si2O8, the materials CaCO3, Al2O3 and SiO2 are weighed respectively, the materials are fully mixed and then ball-milled, and after ball-milling, they are dried, sieved and put into a corundum crucible, and then pre-calcined at a temperature of 850° C. for 5 hours to obtain CaAl2Si2O8 powder;
[0048] 3) The MgTiO3 powder obtained in step 1), the CaAl2Si2O8 powder obtained in step 2) and the sintering aid Bi2O3 are ball-milled and dried in proportion, and then granulated and sieved. The sieved granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm. The cylinders are first sintered at 600°C for 2 h to remove binder, and then sintered at 1330°C for 4.5 h to obtain the microwave dielectric ceramic material.
[0049] Example 4
[0050] The microwave dielectric ceramic material of this embodiment 4 is a multiphase structural ceramic material, including a main crystalline phase and a secondary crystalline phase, the main crystalline phase is MgTiO3, the molar fraction of the main crystalline phase is 0.99; the secondary crystalline phase is CaAl2Si2O8, the molar fraction of the secondary crystalline phase is 0.01. The microwave dielectric ceramic material also includes a sintering aid ZnO, and the sintering aid accounts for 1.5wt.% of the mass of the microwave dielectric ceramic material.
[0051] The method for preparing the high quality factor microwave dielectric ceramic material comprises the following steps:
[0052] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 900° C. for 2.5 hours to obtain MgTiO3 powder;
[0053] 2) According to the molar ratio of each element in the composition expression CaAl2Si2O8, the materials CaCO3, Al2O3 and SiO2 are weighed respectively, the materials are fully mixed and then ball-milled, and after ball-milling, they are dried, sieved and put into a corundum crucible, and then pre-calcined at a temperature of 900° C. for 4.5 hours to obtain CaAl2Si2O8 powder;
[0054] 3) The MgTiO3 powder obtained in step 1), the CaAl2Si2O8 powder obtained in step 2) and the sintering aid ZnO are ball-milled and dried in proportion, and then granulated and sieved. The sieved granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm. The cylinders are first sintered at 600°C for 2 h to remove binder, and then sintered at 1350°C for 4.5 h to obtain the microwave dielectric ceramic material.
[0055] Comparative Example 1
[0056] The microwave dielectric ceramic material of Comparative Example 1 includes MgTiO3 and a sintering aid CuO; the mass fraction of the sintering aid is 3 wt.%.
[0057] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 900° C. for 2.5 hours to obtain MgTiO3 powder;
[0058] 2) The MgTiO3 powder and the sintering aid CuO obtained in step 1) are ball-milled and dried in proportion, and then granulated and sieved. The sieved granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm. The cylinders are first sintered at 600°C for 2 h to remove binder, and then sintered at 1330°C for 3.5 h to obtain the microwave dielectric ceramic material.
[0059] Comparative Example 2
[0060] The microwave dielectric ceramic material of Comparative Example 2 includes a main crystalline phase and a secondary crystalline phase. The main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.95; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.05.
[0061] The method for preparing the microwave dielectric ceramic material comprises the following steps:
[0062] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 830° C. for 4.5 hours to obtain MgTiO3 powder;
[0063] 2) According to the molar ratio of each element in the composition expression CaAl2Si2O8, the materials CaCO3, Al2O3 and SiO2 are weighed respectively, the materials are fully mixed and then ball-milled, and after ball-milling, they are dried, sieved and put into a corundum crucible, and then pre-calcined at a temperature of 850° C. for 5 hours to obtain CaAl2Si2O8 powder;
[0064] 3) The MgTiO3 powder obtained in step 1) and the CaAl2Si2O8 powder obtained in step 2) are ball-milled and dried in proportion, and then granulated and sieved. The sieved granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm. The cylinders are first sintered at 600°C for 2 hours to remove binder, and then sintered at 1370°C for 5 hours to obtain the microwave dielectric ceramic material.
[0065] Comparative Example 3
[0066] The microwave dielectric ceramic material of Comparative Example 3 is MgTiO3 ceramic material.
[0067] The method for preparing the microwave dielectric ceramic material comprises the following steps:
[0068] 1) Weighing materials MgO and TiO2, mixing the materials thoroughly and then ball milling them, drying and sieving them after ball milling, putting them into a corundum crucible, and then pre-calcining them at a temperature of 850° C. for 4.5 hours to obtain MgTiO3 powder;
[0069] 2) The MgTiO3 powder obtained in step 1) is ball-milled and dried, and then granulated and sieved. The sieved granules are then pressed into cylinders with a diameter of 10 mm and a height of 6 mm. The cylinders are first sintered at 600°C for 2 h to remove binder, and then sintered at 1350°C for 6 h to obtain the microwave dielectric ceramic material.
[0070] Performance Testing
[0071] The microwave dielectric properties of the microwave dielectric ceramic material tested using a microwave network analyzer are shown in Table 1.
[0072] Table 1 Parameter values of the embodiments and comparative examples and microwave dielectric properties of microwave dielectric ceramic materials
[0073] Group Sintering temperature(℃) <![CDATA[ε r ]]> Qf(GHz) <![CDATA[τ f (ppm / ℃)]]> Example 1 1280 21.4 64022 6.5 Example 2 1300 22.1 63394 7.1 Example 3 1310 20.5 62883 9.4 Example 4 1320 21.7 61785 12.7 Comparative Example 1 1330 19.5 58067 -18.3 Comparative Example 2 1370 18.7 49230 16.5 Comparative Example 3 1350 18.2 45566 -27.8
[0074] It can be seen from Table 1 that, compared with Comparative Examples 1-3, the microwave dielectric ceramic materials prepared in Examples 1-4 can maintain the following microwave dielectric properties at 1280-1360°C: ε r =21±1, Qf>60000GHz, resonant frequency temperature coefficient τ fThe absolute value is less than 15ppm / ℃. By comparing the examples and the comparative examples, it can be seen that after adding the sintering aid, the sintering temperature can be significantly reduced, thereby improving the production efficiency of the product. By comparing Examples 1-4 with Comparative Examples 1 and 3, it can be seen that the addition of CaAl2Si2O8 will significantly reduce the resonant frequency temperature coefficient, thereby ensuring the temperature stability of the ceramic material. The microwave dielectric ceramic material of the present invention has a high quality factor, a near-zero resonant frequency temperature coefficient, and good temperature stability, which is of great significance for promoting the development of microwave communication technology.
[0075] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any modifications or equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A high quality factor microwave dielectric ceramic material, characterized in that: The microwave dielectric ceramic material is a composite structure ceramic material, including a main crystalline phase and a secondary crystalline phase, wherein the main crystalline phase is MgTiO3, and the molar fraction of the main crystalline phase is 0.93-0.99; the secondary crystalline phase is CaAl2Si2O8, and the molar fraction of the secondary crystalline phase is 0.01-0.
07.
2. A high quality factor microwave dielectric ceramic material according to claim 1, characterized in that: The microwave dielectric ceramic material also includes a sintering aid, which accounts for 0.1 to 5 wt.% of the mass of the microwave dielectric ceramic material; the sintering aid is selected from at least one oxide of Cu, B, Bi, V, Zn, and Li.
3. The high quality factor microwave dielectric ceramic material according to claim 1, characterized in that: The microwave dielectric ceramic material has a dielectric constant of 20 to 22, a quality factor Qf value of not less than 60000 GHz, an adjustable resonant frequency temperature coefficient and an absolute value of ≤15 ppm / °C.
4. A method for preparing a high quality factor microwave dielectric ceramic material according to any one of claims 1 to 3, characterized in that: The steps include: 1) The weighed materials MgO and TiO2 are mixed fully and then ball-milled, and after ball-milling, they are dried, sieved, put into a corundum crucible, and then pre-calcined at a temperature to obtain MgTiO3 powder; 2) The weighed materials CaCO3, Al2O3, and SiO2 are mixed thoroughly and ball-milled, dried, sieved, put into a corundum crucible, and then pre-calcined at a temperature to obtain CaAl2Si2O8 powder; 3) The MgTiO3 powder obtained in step 1) and the CaAl2Si2O8 powder obtained in step 2) are mixed in proportion, ball-milled, dried, granulated, sieved, pressed, and finally debinded and sintered to obtain the microwave dielectric ceramic material.
5. The method for preparing a high quality factor microwave dielectric ceramic material according to claim 4, characterized in that: In step 3), a sintering aid is also added, and the sintering aid is selected from at least one oxide of Cu, B, Bi, V, Zn, and Li.
6. The method for preparing a high quality factor microwave dielectric ceramic material according to claim 4, characterized in that: The pre-burning temperature in step 1) and step 2) is 800-1000° C., and the pre-burning time is 2-5 hours.
7. The method for preparing a high quality factor microwave dielectric ceramic material according to claim 4, characterized in that: The granulation in step 3) is to mix the dried powder with a binder and then make micron-sized spherical particles; the binder used in the granulation is selected from at least one of polyvinyl alcohol solution, polyvinyl butyral solution, acrylic acid solution or methyl cellulose.
8. The method for preparing a high quality factor microwave dielectric ceramic material according to claim 4, characterized in that: In step 3), the granules are pressed into cylinders with a diameter of 10 mm and a height of 6 mm.
9. The method for preparing a high quality factor microwave dielectric ceramic material according to claim 4, characterized in that: The debinding process in step 3) is carried out at 600°C for 2 hours.
10. The method for preparing a high quality factor microwave dielectric ceramic material according to claim 4, characterized in that: The sintering process in step 3) is sintering at 1280-1360° C. for 3-7 hours.